THE IMPACT OF PROJECT-BASED LEARNING ON DEVELOPING CRITICAL THINKING SKILLS AMONG B2 EFL LEARNERS - Bahodirova Durdona Muzaffar kizi (International Journal of Literature and Language Studies, 2026)
This article explores the impact of Project-Based Learning (PBL) on developing critical thinking skills among B2-level learners of English as a Foreign Language (EFL). The study examines how project-based activities improve learners' analytical thinking, problem-solving, decision-making, creativity, and collaborative learning skills. In addition, the paper discusses the educational benefits of integrating PBL into English language teaching and offers practical recommendations for enhancing learners' critical thinking and communicative competence.